N-doped porous carbon from Sargassum spp. as metal-free electrocatalysts for oxygen reduction reaction in alkaline media. (21st December 2017) - Escobar, B.; Pérez-Salcedo, K.Y.; Alonso-Lemus, I.L.; Pacheco, D.; Barbosa, Romeli
Abstract: The use of Sargassum spp. as raw material for the synthesis of metal-free electrocatalyst was studied. Besides, it offers an interesting alternative to low cost commercial activated carbons with applications in generation and storage energy. In this work, physicochemical and electrochemical properties of pyrolyzed, activated and doped carbons synthesized from this abundant seaweed have been studied. Graphitic carbon formation after pyrolysis was confirmed by Raman spectroscopy. SBET increase after activation and doping treatment was corroborated by BET. Electrochemical analyses demonstrated that the SAC sample exhibits the highest ORR activity and showed a current density (4.78 mA cm −2 ) close to commercial 20 wt% Pt/C (5.6 mA cm −2 ) evaluated at the same conditions. Moreover, SDO sample shows the better onset potential (0.852 V vs. RHE), which is in accordance with the content of N-pyridinic bonds on its surface. These results suggest that SDO and SAC biocarbons from Sargassum spp. are a promising cathode material for fuel cells. Highlights: Biomass is an abundant and low-cost source of carbon and nitrogen. Self-doped porous carbon metal-free electrocatalyst synthesized from Sargassum spp. Applied as an electrocatalyst for the oxygen reduction reaction in alkaline medium. Activation process of the pyrolyzed biomass carried out with KOH. Doped Sargassum spp. exhibited BET surface area of 133.871 m 2  g −1 .